1990
DOI: 10.1111/j.1365-2605.1990.tb00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Laminin, type IV collagen, and fibronectin in normal and cryptorchid human testes. An immunohistochemical study

Abstract: An immunohistochemical study of laminin, type IV collagen, and fibronectin was carried out in the testes of normal men and in the cryptorchid and contralateral scrotal testes of cryptorchid men from 2 to 40 years of age. The integrated optical density (IOD) per unit area of the lamina propria was measured in the immunostained sections. Fibronectin was found throughout the thickness of the lamina propria of the seminiferous tubules and in the interstitial connective tissue. No differences between normal and cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…The testicular vasculature also exhibited intense laminin immunostaining, especially in the muscular layer of the medium sized vessels and in the basal lamina of the endothelium. These findings are consistent with numerous approaches that investigated the localization of laminin in the testis of several mammalian species including mouse (Pelliniemi and Frojdman 2001), rat (Gelly et al 1989;El Ouali et al 1991;Pelliniemi and Frojdman 2001), dog (Benazzi et al 1995) and human (Pollanen et al 1985;Davidoff et al 1990;Santamaria et al 1990;Virtanen et al 1997;Gülkesen et al 2002;Ooba et al 2008). Taken together, the localization of laminin in the testis of mammals and birds might point out to its crucial role in the male reproduction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The testicular vasculature also exhibited intense laminin immunostaining, especially in the muscular layer of the medium sized vessels and in the basal lamina of the endothelium. These findings are consistent with numerous approaches that investigated the localization of laminin in the testis of several mammalian species including mouse (Pelliniemi and Frojdman 2001), rat (Gelly et al 1989;El Ouali et al 1991;Pelliniemi and Frojdman 2001), dog (Benazzi et al 1995) and human (Pollanen et al 1985;Davidoff et al 1990;Santamaria et al 1990;Virtanen et al 1997;Gülkesen et al 2002;Ooba et al 2008). Taken together, the localization of laminin in the testis of mammals and birds might point out to its crucial role in the male reproduction.…”
Section: Discussionsupporting
confidence: 90%
“…This interest in the seminiferous tubule extracellular matrix components stems partially from observations that overabundance of laminin is associated with an abnormally thickened lamina propria and is possibly related to male infertility (Davidoff et al 1990;Gülkesen et al 2002;Ooba et al 2008). Previously, numerous approaches have studied the localization of laminin in the testis and epididymis of several mammalian species including mouse (Pelliniemi and Frojdman 2001), rat (Gelly et al 1989;El Ouali et al 1991;Koch et al 1999;Pelliniemi and Frojdman 2001), dog (Benazzi et al 1995), human (Pollanen et al 1985;Davidoff et al 1990;Santamaria et al 1990;Virtanen et al 1997;Gülkesen et al 2002;Ooba et al 2008) and bovine (Abd-Elmaksoud 2005; Alkafafy 2005).…”
Section: Introductionmentioning
confidence: 96%
“…In light of the report by Gülkesen et al 43,. who described a decrease in the diameter of the seminiferous tubules of hypospermatogenic men - a finding they noted had also been seen before in previous studies4445, this suggests that a reduced tubule diameter is correlated with impaired spermatogenesis43. This finding is clinically important as it suggests that success rates of sperm retrieval during testicular sperm extraction (TESE) could be increased by selection of testicular tissue revealing the physiological range of diameter.…”
Section: Discussionsupporting
confidence: 68%
“…Several reports showed that there are heterogeneity in the thickness of the lamina propria in the testes with varicocele, cryptorchidism, and Klinefelter's syndrome (11,17,18). We observed a similar heterogeneity in other cases.…”
supporting
confidence: 60%